Deterioration of wood plastics composites by the white-rot fungus pycnoporus sanguineus - Cesarino, Ivana [UNESP]; Dias, Otávio Augusto Titton; Negrão, Djanira Rodrigues [UNESP]; Rocha, Ligia Linardi Niero [UNESP]; Leão, Alcides Lopes [UNESP] (My University, 2019)
Wood plastic composites (WPC) are characterized by the mixing of wood fibers with plastics, allowing the production of new products whose characteristics are in several aspects superior to those of the original products and represent an expanding class of durable and low-cost materials in which their uses can reduce the environmental footprint and the dependence on petroleum products. Nevertheless, WPC has some setbacks, including biodegradation, which shortens its life span. In this study, the wood composite was exposed to the white-rot fungus Pycnoporus sanguineus in order to evaluate its resistance to biodegradation. The WPC was prepared with a 1:1 ratio of Eucalyptus spp. bark as reinforcement agent and polypropylene as matrix. Mechanical and rheological properties and mass loss were evaluated from 15 to 120 days of fungus exposure. After 15 days, a mass loss was detected, which transmitted a negligible effect on the impact resistance of the composite. For the 120-day fungus-exposed composite, the fungus produced a biofilm under the WPC that create a special environment for lignocellulosic consuming led to deterioration of the mechanical properties and minor changes on the thermal–chemical stability of the WPC. Finally, the study gave a great indication of the susceptibility of a Eucalyptus-based composite to biodegradation.
Keywords: Biobased composites; Biodegradation; Eucalyptus bark; Lignocellulolytic fungus; Wood-plastic composite